Inhibition of Lung Cell Carcinoma Malignity in Vivo via Tumor Cell Transduction by Interferon-β Gene - Lykhova, O. O.; Bezdenezhnykh, N. O.; Saulenko, K. O.; Strokovska, L. I.; Kudryavets, Yu. I. (Problems of Cryobiology and Cryomedicine, 2018)
Probl Cryobiol Cryomed 2018; 28(1): 074–078